2014
DOI: 10.3109/14767058.2014.968842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofLactobacillus reuteriand nystatin prophylaxis onCandidacolonization and infection in very low birth weight infants

Abstract: Prophylactic L. reuteri supplementation is as effective as nystatin, and more effective in reducing the incidence of proven sepsis in addition to its favorable effect on feeding intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
3
27
0
2
Order By: Relevance
“…Roy et al [5] conducted a prospective, randomized, double blind trial involving preterm neonates and revealed that probiotic supplementation (a mix of L. acidophilus, Bifidobacterium longum, B. bifidum and B. lactis) led to reduced enteral fungal colonization, reduced invasive fungal sepsis, earlier establishment of full enteral feeds, and reduced duration of hospital stay. These results were similar to those published by Oncel et al [1].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Roy et al [5] conducted a prospective, randomized, double blind trial involving preterm neonates and revealed that probiotic supplementation (a mix of L. acidophilus, Bifidobacterium longum, B. bifidum and B. lactis) led to reduced enteral fungal colonization, reduced invasive fungal sepsis, earlier establishment of full enteral feeds, and reduced duration of hospital stay. These results were similar to those published by Oncel et al [1].…”
supporting
confidence: 83%
“…We read with interest a recently published study in this journal by Oncel et al [1] entitled ''Comparison of Lactobacillus reuteri (L. reuteri) and nystatin prophylaxis on Candida colonization and infection in very low birth weight (VLBW) infants''. In this prospective, randomized comparative study involving preterm infants (n¼300) with a gestational age of 32 weeks and birth weight of 1500 g, it was concluded that prophylactic orally administered L. reuteri was as effective as nystatin in prevention of fungal colonization and invasive candidiasis (IC).…”
mentioning
confidence: 98%
“…23e26, 43,44 Two recent trials reported that prophylactic supplementation of Saccharomyces boulardii or Lactobacillus reuteri was as effective as nystatin in preventing fungal colonization and IFIs in preterm neonates in NICUs. 45,46 The efficacy of a mixture of species of probiotics in preventing rectal colonization by Candida was also investigated and confirmed in critically ill children in a pediatric intensive care unit. 33 Moreover, several trials have reported that probiotics are effective in preventing and treating vulvovaginal candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two trials compared probiotics with nystatin regarding their effects on fungal infection in preterm infants. Oncel et al 45 and Demirel et al 46 consistently concluded that supplementation of Lactobacillus reuteri or Saccharomyces boulardii was as effective as nystatin with respect to fungal colonization and IFIs, and more effectively reduced the incidence of sepsis, duration of hospitalization, and feeding intolerance. Moreover, updated meta-analyses have confirmed the efficacy and safety of probiotics in preventing necrotizing enterocolitis and late-onset sepsis in preterm neonates.…”
Section: Implications For Practicementioning
confidence: 99%
“…An RCT by Roy et al 35 demonstrated that supplementation with a mix of multiple probiotics (a mix of L. acidophilus , B. longum , Bifidobacterium bifidum , and Bifidobacterium lactis ) in preterm infants and neonates led to reduced enteral fungal colonization and invasive fungal sepsis, earlier establishment of full enteral feeds, and reduced duration of hospital stay. More recently, Oncel et al 36 , in a RCT, demonstrated that prophylactic oral administration of L. reuteri in preterm infants (gestational age of not more than 32 weeks and birth weight of not more than 1500g) was as effective as nystatin in the prevention of fungal colonization and invasive candidiasis and reduced the incidence of sepsis, feeding intolerance, and duration of hospitalization.…”
Section: Probiotic Use In Critically Ill Childrenmentioning
confidence: 99%